COMPARATIVE DESCRIPTION OF THE BINDING SPECIFICITY OF RECEPTORS OF STRUCTURAL COMPONENTS OF THE GLANDULAR ZONE MUCOSA OF THE RAT HARD PALATE USING Α-GALACTOSE-SPECIFIC SOYBEAN LECTIN - Yeroshenko, G.A.; Tymoshenko, Yu.V.; Kulai, О.O.; Shevchenko, K.V.; Zviahilska, I.M.; Kopantseva, L.M.; Khilinska, T.V. (World of Medicine and Biology, 2024)
The paper presents the data of a lectinochemical study of the components of the mucous membrane of the glandular zone of the dura mater of rats with the help of α-galactose-specific soybean lectin. It was found that increased expression of receptors for α-galactose-specific lectin of soybean seeds was determined in the spiky, granular layers to a strong degree, in the basal layer the degree of binding remained constant, compared to the 14th day of observation. It increased from weak to moderate on the part of the basement membrane. The reaction from the mast cells remained strong. Therefore, the changes that occur under the influence of a 1 % solution of methyl ether of methacrylic acid on the mucous membrane of the hard palate should indicate changes in the structural components of this zone, which leads to a violation of the function of the minor salivary glands and the development of a pathological process. The α-galactose-specific lectin of soybean seeds can be a marker of these processes.
Keywords: oral mucosa; secretory activity; salivary glands; hard palate; methyl methacrylate; soybean lectin (SBA)